Loneliness and subjective evaluations of physical health: the underlying mechanism of body image - Tian, Michelle Nee Chow,; Pei, Hwa Goh,; Koh, Darlene M.,; Khanifam, Mehrdad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Loneliness has been shown to have robust associations with our health. However, little is known about the degree to which loneliness shapes our perceptions of physical health, which has been shown to have unique contributions to our overall health status. Therefore, this study aimed to examine the relationship between loneliness and perceived physical health. We tested body image as a potential underlying mechanism unique to this relationship, while accounting for the previously established mechanisms of stress and self-esteem. For comparison purposes, we tested this model with depression and anxiety as outcome variables. 319 Malaysian young adults (133 males and 186 females) aged 23.05 on average completed an online questionnaire containing our measures. Results revealed that higher loneliness was associated with higher depression, higher anxiety, and lower perceived physical health. Parallel mediation analyses showed that there were significant indirect effects of loneliness on perceived physical health and psychological outcomes through perceived stress and self-esteem. Indirect effects through body image were only significant for perceived physical health and not for psychological outcomes. Overall, these findings highlight the value of reducing stress and improving self evaluations, particularly body image, in healthcare interventions designed to mitigate the health-debilitating effects of prolonged loneliness in young adults.